Improving the Efficiency of Coagulation-Flocculation in Removing Organic Matter from Water with pH Optimization and Granular Activated Carbon Filtration - Ennouhi, Mariem; Aggadi, Sanaa El; Mabrouki, Jamal; Belmaghraoui, Walid; Qisse, Najat; Boutakiout, Amale; Belghiti, Mohammed Alaoui El (Journal of Environmental Accounting and Management, 2026)
The olive tree is a major fruit crop in the Mediterranean Sea area and is responsible for 95% of the world’s olive oil production. However, the disposal of the waste generated during olive oil production, known as mill effluent (ME), into rivers leads to surface water pollution. To address this issue, coagulation-flocculation with aluminium sulphate and ferric chloride were tested to reduce the organic matter in ME-contaminated water. The study found that for the same dose of 70 mg.L-1, ferric chloride and aluminium sulphate reduced the organic matter expressed in terms of oxidability by 69.85% and 52.94%, respectively. Prechloration improved the reduction rate of organic matter expressed in terms of oxidability by 12% for aluminium sulphate and around 9% for ferric chloride. Combining coagulants (aluminium sulfate, ferric chloride) with lime further improved the removal rate of organic matter. The organic material removal rate was 50% for 8 mg.L-1 of chlorine, 70 mg.L-1 of aluminum sulfate, and 23.3 mg.L-1 of lime at pH 7.42, while ferric chloride and lime resulted in a 52.38% organic matter removal rate for 8 mg.L-1 of chlorine, 50 mg.L-1 of ferric chloride, and 33.5 mg.L-1 of lime at pH 7.02. These results indicate that coagulation-flocculation with aluminium sulphate and ferric chloride could provide a sustainable approach for reducing water pollution and ensuring efficient use of resources.